2001
DOI: 10.1016/s1386-6532(01)00168-8
|View full text |Cite
|
Sign up to set email alerts
|

Baculovirus expression of parvovirus B19 (B19V) NS1: utility in confirming recent infection

Abstract: Background: The presence of anti-parvovirus B19 (B19V) IgM against viral capsid proteins (VP1 and VP2) has long been used to detect recent infection. The utility of antibodies directed against B19V NS1 protein has received less attention as a serological indicator of recent infection, although anti-B19V NS1 IgG has been associated with persistent infection. Objecti6es: To elucidate the role of anti-B19V NS1 antibody detection in recent infection, full-length B19V NS1 was expressed and purified. The resultant a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2002
2002
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 16 publications
(20 reference statements)
1
23
0
Order By: Relevance
“…Production and purification of recombinant S. mansoni LAP in baculovirus expression vector system Spodoptera frugiperda (Sf 9 ) insect cells (Invitrogen) were transformed with pBlueBac4.5 plasmid construct incorporating the S. mansoni LAP cDNA as previously described (Ennis et al, 2001). Cell suspensions were lysed in the presence of 0.05% (v/v) Tween w 20 (Sigma) detergent in 50 mM NaH 2 PO 4 , 300 mM NaCl, and 10 mM imidazole (pH 8.0, lysis buffer), and then incubated on ice for 30 min.…”
Section: Construction Of Cdna Expression Vectormentioning
confidence: 99%
“…Production and purification of recombinant S. mansoni LAP in baculovirus expression vector system Spodoptera frugiperda (Sf 9 ) insect cells (Invitrogen) were transformed with pBlueBac4.5 plasmid construct incorporating the S. mansoni LAP cDNA as previously described (Ennis et al, 2001). Cell suspensions were lysed in the presence of 0.05% (v/v) Tween w 20 (Sigma) detergent in 50 mM NaH 2 PO 4 , 300 mM NaCl, and 10 mM imidazole (pH 8.0, lysis buffer), and then incubated on ice for 30 min.…”
Section: Construction Of Cdna Expression Vectormentioning
confidence: 99%
“…B19 recombinant proteins VP1, VP2, and NS1 were produced in, and purified from, Spodoptera frugiperda (Sf9) insect cells infected with recombinant baculovirus encoding either VP1, VP2, or NS1 open-reading frames, as described elsewhere [10,[14][15][16].…”
Section: Study Population Heparinized Venous-blood Samples (10 Ml;mentioning
confidence: 99%
“…In fact, specific IgG against linear epitopes of VP2 disappears within 6-12 months after infection [8]. More dramatically, there is a near-total diminution of NS1-specific IgG in previously infected individuals [10]. It is, therefore, firmly established that detection of B19-specific IgG against conformational epitopes is currently the most reliable method for the detection of previous infection with, and probable immunity to, B19.…”
mentioning
confidence: 99%
“…Although initially thought to be a marker of persistent infection only [von Poblotzki et al, 1995], the detection of NS1 IgG has also been shown to be present during acute B19 infection in 61%-69% of individuals [Hemauer et al, 2000;Ennis et al, 2001]. Moreover, significant T cell responses to NS1 have also been reported in recently infected individuals and patients who developed chronic arthropathy following B19 infection [Mitchell et al, 2001].…”
Section: Discussionmentioning
confidence: 99%